Gender Disparity in 12-lead Electrocardiogram Acquisition by Emergency Medical Service Staff for Patients With Cardiac-type Chest Pain - Henderson, Bronwyn (Auckland University of Technology, 2016)
Background: Female patients suffering from Acute Coronary Syndrome (ACS) receive fewer investigations and treatments than male patients, in both the pre-hospital and hospital environments. To accurately diagnose ACS a 12-Lead ECG is required and failure to acquire an early 12-lead ECG can impact on accessing timely treatment. This could be a barrier to women receiving appropriate medical care. Some authors suggest that, because female patients suffering ACS are more likely to present with atypical symptoms, their cardiac diagnosis is missed. Consequently, they receive inferior treatment to their male counterparts. Unlike previous studies exploring gender disparity in investigation of ACS, this study controlled for both the EMS staff member's working diagnosis and the patient’s presentation. The primary objective was to establish whether EMS staff exhibited gender disparity when assessing patients with cardiac-type chest pain, though 12-lead ECG acquisition rates when the attending EMS staff member’s working diagnosis was that of ACS. Secondary objectives were to investigate procedural compliance, variables associated with reduced odds of 12-lead ECG acquisition and whether previously proposed explanations of gender disparity in ACS assessment were supported. Methods and Results: Intensive Care Paramedics, trained in data extraction, reviewed 26,273 patient report forms (PRFs) from four urban and rural centres across New Zealand. Study inclusion was limited to PRFs from patients who described cardiac-type chest pain and where the EMS staff member’s working diagnosis was that of ACS. Partial verification double-entry was used to lower error rates whilst maintaining cost-effective data extraction for PRFs collected over a one year period (ending in November 2010). A power calculation was undertaken based on data from a 2009 pilot study. This established that a minimum of 418 PRFs would be required to detect a difference in acquisition rates between male and female patients (α=0.05, power=90%). A total of 1,675 PRFs met the study’s inclusion criteria and were included in the study; 52% were from male patients. Overall rates of 12-lead ECG acquisition were low at 42% of cases. 50% of males (n=431) had a 12-lead ECG acquired compared with 34% of females (n=275) (P<0.001). After adjusting for potential confounders in a multiple logistic regression model, the odds ratio for female patients having a 12-lead ECG acquired was 0.50 (CI95%, 0.40 – 0.63) compared with male patients. The probability of having a 12-lead ECG acquired for both genders combined varied significantly between study centres, from 86% of the sample from the Rural B region to 33% of the sample from the Urban B region. Conclusions This study showed that the established gender disparity in ACS investigations cannot be fully explained by women’s increased propensity for an atypical-ACS-presentation. Furthermore, a false negative ACS diagnosis on the basis of this atypical-presentation cannot fully explain the gender disparity either. We showed that when the patient’s presentation and the EMS staff member’s diagnosis were controlled for, female patients still had significantly fewer 12-lead ECGs acquired than male patients. Secondary analysis identified substantial local variation in practice, suggesting the possibility of improving the frequency of this vital investigation in ACS through culture change.
Keywords: Paramedic; EMS; Acute Coronary Syndrome; Chest pain; ECG; Electrocardiogram; Cardiac; Treatment; New Zealand; Emergency; Gender disparity; 12-lead; AMI; Myocardial Infarction; Ambulance